Impact of metformin on the clinical and metabolic parameters of women with polycystic ovary syndrome: a systematic review and meta-analysis of randomised controlled trials. (October 2022) - Abdalla, Mohammed Altigani; Shah, Najeeb; Deshmukh, Harshal; Sahebkar, Amirhossein; Östlundh, Linda; Al-Rifai, Rami H.; Atkin, Stephen L.; Sathyapalan, Thozhukat
Context: Polycystic ovary syndrome (PCOS) is one of the commonest endocrine disorders affecting women of reproductive age, and metformin is a widely used medication in managing this condition. Aim: To review the available literature comprehensively on the therapeutic impact of metformin on the clinical and metabolic parameters of women with PCOS. Data source: We searched PubMed, MEDLINE, Scopus, Embase, Cochrane Library and the Web of Science and selected sources for grey literature from their inception to April 2020. An updated search in PubMed was performed in June 2022. Data synthesis: Two reviewers selected eligible studies and extracted data, and the review is reported following the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: In 24 eligible randomised controlled trials (RCTs) involving 564 participants who received metformin therapy, metformin was associated with significant reduction in body weight by 3.13 kg (95% CI: −5.33, −0.93), body mass index (BMI) by 0.82 kg/m² (95% CI: −1.22, −0.41), fasting blood glucose [standardised mean difference (SMD): −0.23; 95% CI: −0.40, −0.06], low-density lipoprotein cholesterol (LDL-C) (SMD: −0.41; 95% CI: −0.85, 0.03), total testosterone (SMD: −0.33; 95% CI: −0.49, −0.17), androstenedione (SMD: −0.45; 95% CI: −0.70, −0.20), 17-hydroxyprogesterone (17-OHP) (SMD: −0.58; 95% CI: −1.16, 0.00) and increase the likelihood of clinical pregnancy rate [odds ratio (OR): 3.00; 95% CI: 1.95, 4.59] compared with placebo. Conclusion: In women with PCOS, metformin use has shown a positive impact in reducing body weight, BMI, total testosterone, androstenedione, 17-OHP, LDL-C, fasting blood glucose and increasing the likelihood of pregnancy in women with PCOS.